Groundwater geochemistry, hydrogeology and potash mineral potential of the Lake Woods region, Northern Territory, Australia. Issue 3 (3rd April 2019) - de Caritat, P.; Bastrakov, E. N.; Jaireth, S.; English, P. M.; Clarke, J. D. A.; Mernagh, T. P.; Wygralak, A. S.; Dulfer, H. E.; Trafford, J.
Abstract: We collected 38 groundwater and two surface-water samples in the semi-arid Lake Woods region of the Northern Territory to better understand the hydrogeochemistry of this system, which straddles the Wiso, Tennant Creek and Georgina geological regions. Lake Woods is presently a losing waterbody feeding the underlying groundwater system. The main aquifers comprise mainly carbonate (limestone and dolostone), siliciclastic (sandstone and siltstone) and evaporitic units. The water composition was determined in terms of bulk properties (pH, electrical conductivity, temperature, dissolved oxygen, redox potential), 40 major, minor and trace elements, and six isotopes (δ 18 Owater, δ 2 Hwater, δ 13 CDIC, δ 34 SSO4 2–, δ 18 OSO4 2–, 87 Sr/ 86 Sr). The groundwater is recharged through infiltration in the catchment from monsoonal rainfall (annual average rainfall ∼600 mm) and runoff. It evolves geochemically mainly through evapotranspiration and water–mineral interaction (dissolution of carbonates, silicates and to a lesser extent sulfates). The two surface waters (one from the main creek feeding the lake, the other from the lake itself) are extraordinarily enriched in 18 O and 2 H isotopes (δ 18 O of +10.9 and +16.4‰ VSMOW, and δ 2 H of +41 and +93‰ VSMOW, respectively), which is interpreted to reflect evaporation during the dry season (annual average evaporation ∼3000 mm) under low humidity conditions (annual average relative humidity ∼40%). This interpretation is supported by modelling results. The potassium (K) relative enrichment (K/Cl – mass ratio over 50 times that of sea water) is similar to that observed in salt-lake systems worldwide that are prospective for potash resources. Potassium enrichment is believed to derive partly from dust during atmospheric transport/deposition, but mostly from weathering of K-silicates in the aquifer materials (and possibly underlying formations). Further studies of Australian salt-lake systems are required to reach evidence-based conclusions on their mineral potential for potash, lithium, boron and other low-temperature mineral system commodities such as uranium.